Kajian Desain Elemen Interior untuk Yayasan Pendidikan Anak Buta di Surabaya - Cindy Fransisca; Sherly de Yong; Purnama Esa Dora Tedjokoesomo (Intra, 2018)
Blind get the opportunity to be guided and get a chance to get education to grow optimally. Blind people are individuals who have visual inhibitions. Limitations impede blind children in various activities in fulfilling their needs, so in addition to requiring public education services as well as a child, the blind child needs special services to rehabilitate the disorder, it is obligatory for a blind child to receive special attention. Related to that, it takes an interior element that can be used to facilitate blind children in doing activities, especially in learning activities. The purpose of this study is to describe the proposals, solutions and roles of the creation of furniture design for blind children at the Blind Children's Education Foundation Surabaya. Target of research that resulted, among others, in the form of data that has been tested about the design of furniture for children with special needs, especially blind children in the Foundation for Children's Education Buta Surabaya.